2020
DOI: 10.2147/ott.s245178
|View full text |Cite
|
Sign up to set email alerts
|

<p>Review of Research on the Role of Irisin in Tumors</p>

Abstract: Irisin is a newly discovered exercise-induced cytokine, produced by the proteolytic hydrolysis of fibronectin type III domain-containing protein 5 (FNDC5). Irisin is widely distributed in the human body and is involved in the browning of white adipose tissue, improving insulin resistance, improving cognitive function, and regulating bone metabolism. Recent studies have shown that irisin concentration is elevated in a variety of tumor tissues as compared with that in normal tissues. However, irisin has differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 49 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…However, irisin also appears to have a positive effect on cognitive function and to play a role in bone metabolism regulation [2,123]. Finally, recent studies have shown that malignant cells have a higher concentration of irisin than normal ones [124]. Irisin function is apparently contradictory because it is able to induce both cytoprotection and cell death in a plasma concentration-dependent manner.…”
Section: Irisinmentioning
confidence: 99%
“…However, irisin also appears to have a positive effect on cognitive function and to play a role in bone metabolism regulation [2,123]. Finally, recent studies have shown that malignant cells have a higher concentration of irisin than normal ones [124]. Irisin function is apparently contradictory because it is able to induce both cytoprotection and cell death in a plasma concentration-dependent manner.…”
Section: Irisinmentioning
confidence: 99%
“…The biological effects of the botanical oils on insect pests may attribute to their effect on the insect neuro endocrine system and juvenile hormone leading to hormone unbalance occurring malformation and decreasing moths fecundity and egg fertility resembling the effect of the growth regulators as concluded by Sharaby, A. and A. El-Nojiban [29]. Huang et al [30] attributed decreasing of fecundity and fertility to decreasing in periods and time of adults mating which lead to decreasing of ovulation, essential oils have neuro toxic, citotoxic and mutagenic actions among other different insects as investigated by Isman, M.B. ; S. Miresmailli and C.…”
Section: Effects Of Peppermint Oil Nano-formulations On Different Biomentioning
confidence: 99%
“…The studies are presented chronologically, and summary data tables are included. It should be noted that a number of related past reviews exist [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]; however, the present review provides updated information and adds to the existing literature.…”
Section: Introductionmentioning
confidence: 99%